SINERGITAS THREE MARTA PENDIDIKAN DALAM MENGHADAPI JUVENILE DELIQUENCY DI SEKOLAH - Abdullah Abdullah; Khairunnisa’ Hamdani (Khazanah Pendidikan, 2020)
ABSTRACTPuberty its time when kids turns into adult. When in that phase they will havediffrent experiences a level of change on cognitive, affective, and motoric system.Teenagers need a direction, guidance, and also good education from his surrounding,like their family's , their schools or from people's. This research method uses qualitativewith case studies and descriptive type with interviews and observation. The objectives ofThis research is for how far their role facing the juvenile delinquency synergy eachother from teachers, parents and peoples in MA husnur Riayah kembangkuso suboh situbondo hopefully it can overcome and minimizing the juvenile delinquency so they willhave effective education progress. How to face or teacher Countermeasures the juveniledelinquency is : motivational lecture to student, Bp guidance, parents meeting. How isthe best option for parents to face the juvenile delinquency is to become their best friend.Teaching kids aboit religion, make a happy family's, observe their intercommunication.Understanding their behavior, become good examples for them. And how people's toface juvenile delinquency is making village programs for teenagers likr BLK (worktraning center) also having positive activity with good people's like kifaya gathering,sholawat nariyah, sholawat diba’i dan khotmil quran which leading by village people'sfigure.Keyword: teacher, parent, people's, juvenile delinquency.